Study on Left Ventricular Diastolic Dysfunction in Atrial Fibrillation Patients without Structural Cardiac Disease - Marincu, Iosif; Vidican, Iulia; Avram, Valentina Elena; Timircan, Madalina; Suciu, Oana (New Frontiers in Medicine and Medical Research Vol. 15, 2021)
Background: Hypertension and left ventricular hypertrophy (LVH) are most important contributors to left ventricular diastolic dysfunction (DD), left atrial remodeling and atrial fibrillation. Objectives: The primary goal is to compare left atrial (LA) remodelling and left ventricular DD in patients with or without paroxysmal atrial fibrillation (PAF) and with or without essential hypertension (HTN). Materials and Method: The study comprised 128 patients with normal left ventricular systolic function (LVEF\(\ge\)50%). They were divided into two groups based on the presence or absence of essential hypertension. The normotensive individuals (n=65) were split into two groups: PAF (n=32) and control no-PAF (n=33).The hypertensive individuals were further split into two groups: PAF (n=32) and control no-PAF (n=31). The patients in the control group were chosen to match the PAF groups in terms of gender, age, and weight. Resting 12 lead ECG, 24 hour Holter ECG monitoring, 24 hour blood pressure monitoring, and 2D Doppler echocardiography were used to evaluate the patients. The follow-up was done every six months for three years. The MedCalc 12.3.0.0 statistical software for Windows was used for the statistical analysis. When the p-value was less than 0.05, the results were considered statistically significant. Results and Conclusion: PAF patients have larger LA diameters. HTN causes an increase in supplemental LA.The number of PAF episodes has no effect on LA diameters. The gender of the patients has little effect on the statistical data, with larger diameters in PAF and HTN patients.